2020
DOI: 10.3390/antibiotics9090632
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bloodstream Infections Due to Gram-Negative Bacteria with Difficult-to-Treat Resistance

Abstract: The rising incidence of bloodstream infections (BSI) due to Gram-negative bacteria (GNB) with difficult-to-treat resistance (DTR) has been recognized as a global emergency. The aim of this review is to provide a comprehensive assessment of the mechanisms of antibiotic resistance, epidemiology and treatment options for BSI caused by GNB with DTR, namely extended-spectrum Beta-lactamase-producing Enterobacteriales; carbapenem-resistant Enterobacteriales; DTR Pseudomonas aeruginosa; and DTR Acinetobacter baumanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 83 publications
0
42
0
Order By: Relevance
“…Carbapenemase-producing Klebsiella pneumoniae (CP-Kp) has become a significant global public health challenge [ 1 ]. The arrival of novel beta-lactam/beta-lactamase inhibitor combinations, such as ceftazidime/avibactam, meropenem/vaborbactam, imipenem/cilastatin/relebactam, the siderophore cephalosporin, cefiderocol, and a next-generation aminoglycoside, plazomicin, has increased the available treating options in our arsenal, improving the outcome of such infections [ 2 ]. Previously, the available antimicrobial treatment options were colistin, tigecycline, aminoglycosides, fosfomycin, and carbapenems [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenemase-producing Klebsiella pneumoniae (CP-Kp) has become a significant global public health challenge [ 1 ]. The arrival of novel beta-lactam/beta-lactamase inhibitor combinations, such as ceftazidime/avibactam, meropenem/vaborbactam, imipenem/cilastatin/relebactam, the siderophore cephalosporin, cefiderocol, and a next-generation aminoglycoside, plazomicin, has increased the available treating options in our arsenal, improving the outcome of such infections [ 2 ]. Previously, the available antimicrobial treatment options were colistin, tigecycline, aminoglycosides, fosfomycin, and carbapenems [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to original research studies, the Special Issue includes two comprehensive reviews of the management of Gram-negative bacterial infections. Bassetti and colleagues summarize various beta-lactam resistance mechanisms and discuss antimicrobial treatment options for BSI due to Gram-negative bacteria with DTR [ 29 ]. The authors objectively review novel antimicrobial agents, examine the activity of these agent for various antimicrobial resistance mechanisms, and provide insight into the role of these agents in clinical practice [ 29 ].…”
mentioning
confidence: 99%
“…Bassetti and colleagues summarize various beta-lactam resistance mechanisms and discuss antimicrobial treatment options for BSI due to Gram-negative bacteria with DTR [ 29 ]. The authors objectively review novel antimicrobial agents, examine the activity of these agent for various antimicrobial resistance mechanisms, and provide insight into the role of these agents in clinical practice [ 29 ]. Since the respiratory tract is one of the most common sources of Gram-negative bacteria with DTR, Martin-Loeches summarizes current concepts in the management of community-acquired and ventilator-associated pneumonia in intensive care units [ 30 ].…”
mentioning
confidence: 99%
“…Newer antimicrobials might offer an important adjunction in our already limited armamentarium, since they have shown high rates of in vitro susceptibility in isolates resistant to many currently used antimicrobials. The majority of newer antimicrobials are beta-lactam/beta-lactamase inhibitor combinations with variable activity against different types of carbapenemase genes, a novel cephalosporin (cefiderocol), a novel aminoglycoside (plazomicin), and a novel tetracycline (eravacycline) [ 20 ]. Two studies from Greece showed that 100% and 94.3% of K. pneumoniae isolates were susceptible to cefiderocol and plazomicin, respectively [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%